Brøset Violence Checklist (BVC) versus Dynamic Appraisal of Situational Aggression-Inpatient Version (DASA-IV): their sensitivity, specificity and accuracy as a predictor of violence in 24 hours among schizophrenia patients - Yuniati, Wahyu; Putra, Kuswantoro Rusca; Widasmara, Dhelya (Universitas Muhammadiyah Purwokerto, 2020)
Background: Brøset Violence Checklist (BVC) and Dynamic Appraisal of Situational Aggression-Inpatient Version (DASA-IV) are risk assessment instruments of violence that nurses can use in psychiatric services, but their accuracy of the instruments in predicting violent behavior in 24 hours need to be tested.Objective: This study aims to examine the sensitivity and specificity of BVC and DASA-IV instruments in predicting violent behavior within 24 hours and which is more accurate.Method: This is a diagnostic study with a cross-sectional approach. The sample of this study was 112 patients. The respondents' behaviors were observed, based on parameters assessed by BVC and DASA-IV as well as recording incidents of violent behavior using AOS (Aggression Observation Short) as the gold standard. Sensitivity, specificity, and Receiver Operating Characteristic (ROC) tests were conducted to assess the accuracy of the two instruments in predicting violent behavior within 24 hours.Results: 23.2% of the respondents in this study experienced violent behavior in the first 24 hours. BVC has a sensitivity value of 65.4% and specificity of 94.5%. DASA-IV has a sensitivity value of 69.2% and a specificity of 95.5%. The level of accuracy of BVC is 87.9%, and of DASA-IV is 92.2%.Conclusion: DASA-IV is more sensitive, higher in its specificity, and is more accurate in predicting violent behavior within 24 hours in schizophrenic patients compared to BVC